Fluorescence-based thermal sensing with elastic organic crystals - Li, Liang (2022)
Operation of temperature sensors over extended temperature ranges, and particularly in extreme conditions, poses challenges with both the mechanical integrity of the sensing material and the operational range of the sensor. With an emissive bendable organic crystalline material, here we propose that organic crystals can be used as mechanically robust and compliant fluorescence-based thermal sensors with wide range of temperature coverage and complete retention of mechanical elasticity. The exemplary material described remains elastically bendable and shows highly linear correlation with the emission wavelength and intensity between 77 K to 277 K, while it also transduces its own fluorescence in active waveguiding mode. This universal new approach expands the materials available for optical thermal sensing to a vast number of organic crystals as a new class of engineering materials and opens opportunities for the design of lightweight, organic fluorescence-based thermal sensors that can operate under extreme temperature conditions such as are the ones that will be encountered in future space exploration missions.